IL-2/B7.1 (CD80) fusagene transduction of AML blasts by a self-inactivating lentiviral vector stimulates T cell responses in vitro: a strategy to generate whole cell vaccines for AML. - Chan, L; Hardwick, N; Darling, D; Galea-Lauri, J; Gäken, J; Devereux, S; Kemeny, M; Mufti, G; Farzaneh, F (2005)
Combined expression of costimulatory factors and proinflammatory cytokines stimulate effective immune-mediated tumor rejection in a variety of murine tumor models. Specifically, syngeneic tumor cells genetically modified to express B7.1 (CD80) have been shown to induce rejection of previously established murine solid tumors, and transduction with IL-2 can further increase survival. However, poor rates of gene transfer and inefficient expression of multiple transgenes encoded by single vectors have hampered the development of such autologous tumor cell vaccines for clinical trials in acute myeloid leukemia (AML) patients. Here we describe the development of a self-inactivating lentiviral vector encoding B7.1 and IL-2 as a single fusion protein postsynthetically cleaved to generate biologically active membrane-anchored B7.1 and secreted IL-2. This enables the efficient transduction of both established and primary AML blasts, resulting in expression of the transgenes in up to 98% of the cells following a single round of infection at an m.o.i. of 10. The combined expression of IL-2 and B7.1 in AML blasts enables increased stimulation of both allogeneic and autologous T cells. The stimulated lymphocytes secrete greater levels of Th1 cytokines and show evidence of specificity, as indicated by their increased proliferation in the presence of autologous AML compared to remission bone marrow cells.